Performance of Homebalance Test in an Assessment of Standing Balance in Elderly Adults - Kajzar, Jiří; Janatová, Markéta; Hill, Martin; Otáhal, Jakub; Nechlebová, Eva; Tichý, Miroslav; Krejčí, Milada (Physiological research, 2022)
Balance control is a critical task of daily life, the ability to maintain upright posture becomes of particular concern during aging when the sensory and motor system becomes deteriorated. Falls contribute to the most deaths caused by injury within the aged population, and the mortality rate following a fall is drastically elevated. Longitudinal and reliable assessment of balance control abilities is a critical point in the prediction of increased risk of falling in an elderly population. The primary aim of the study was to evaluate the efficiency of the Homebalance test in the identification of persons being at higher risk of falling. 135 subjects (82 women and 53 men) with geriatric syndrome have been recruited and the Homebalance and the Tinetti Balance test were performed. Results of both tests strongly correlated proving the good performance of the Homebalance test. Standing balance declines with increasing body mass index in both genders. Analysis of fluctuations of the center of pressure (COP) revealed higher frequency and magnitude in mediolateral direction COP movements when compared women to men. A strong negative correlation has been found between Tinetti static balance score and the total length of the COP trajectory during the examination on Homebalance (r = -0.6, p<0.001). Although both methods revealed good performance in detecting balance impairment, Homebalance test possesses higher precision due to the continuous nature of COP-derived parameters. In conclusion, our data proved that the Homebalance test is capable to identify persons with impaired balance control and thus are at higher risk of falling.
Keywords: Aging; dospělí; Adult; Postural Balance; lidé; ženské pohlaví; index tělesné hmotnosti; Body Mass Index; úrazy pádem; posturální rovnováha; Aged; Humans; senioři; Accidental Falls; mužské pohlaví; Male; stárnutí; Female